2014
DOI: 10.1111/liv.12466
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of monocarboxylate transporter 4 in tumour cells predicts an unfavourable outcome in patients with hepatocellular carcinoma

Abstract: Aberrant expression of MCT4 in carcinoma cells serves as a novel, independent prognostic factor for HCC, indicating a poorer patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 28 publications
9
38
0
Order By: Relevance
“…According to data acquired from the TCGA database, MCT4 is expressed at higher levels in ESCC cancerous tissue compared with normal tissue. It is possible that MCT4 may act as an oncogene in ESCC, as it does in other types of cancer (11,12,(14)(15)(16)(17)(18)(19) and it could be a potential prognostic factor for ESCC. Analysis of the associations between patient clinicopathological characteristics and MCT4 expression revealed that MCT4 expression was significantly associated with T stage, N stage and TNM stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to data acquired from the TCGA database, MCT4 is expressed at higher levels in ESCC cancerous tissue compared with normal tissue. It is possible that MCT4 may act as an oncogene in ESCC, as it does in other types of cancer (11,12,(14)(15)(16)(17)(18)(19) and it could be a potential prognostic factor for ESCC. Analysis of the associations between patient clinicopathological characteristics and MCT4 expression revealed that MCT4 expression was significantly associated with T stage, N stage and TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of MCT4 in cancer or stromal cells in the tumor microenvironment varies among different types of cancer. Overexpression of MCT4 in both epithelial and stromal cells of breast cancer (11)(12)(13), hepatocellular cancer cells (14,15) and pancreatic cancer cells (16) predicted worse outcomes for patients. Furthermore, high expression of MCT4 in stromal cells of colorectal cancer (17), oral squamous cell carcinoma (18) and gastric cancer (19) was revealed to be associated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these results pointed out MCT4 as a potential marker for tumor aggressiveness, as suggested in other tumor types. [48][49][50][51] Furthermore, the authors suggest that MCT4 may act as a prognosis predictor due to its association with overall survival. 25 In the present study, there was no association between MCT4 and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The role of over-expressed MCT4 in HCC has been illustrated. It is associated with HCC progression and poor prognosis[48,49]. The latest study observed the reduced expression of MCT1 and MCT2 in HCC[50].…”
Section: Reprogramming Of Glucose Metabolism-related Enzymes and Tranmentioning
confidence: 99%